Therapeutic effects of melatonin on an ovalbumin-induced allergic rhinitis model in rats. Issue 6 (December 2021) - Cakir Cetin, Asli; Ecevit, Mustafa Cenk; Gumustekin, Mukaddes; Pekcetin, Cetin; Ozbal, Seda; Efe, Hande; Koca, Pelin; Akcay, Ozge; Tuncok, Yesim
Abstract: Objective: We aimed to investigate the therapeutic effects of melatonin in an experimental AR model. Methods: Thirty-two Wistar rats were randomised into four groups ( n  = 8 each). The experimental AR model was established in the saline (SF), ethanol, and melatonin groups via intraperitoneal (i.p.) injections and intranasal application of ovalbumin. The SF, ethanol, and melatonin groups received daily i.p. saline, 2% ethanol dissolved in saline, and 10 mg/kg melatonin dissolved in 2% ethanol and saline. The control group received the same amount of i.p. and intranasal saline. Total nasal symptom scores were recorded in all rats on days 1 (baseline), 15, 20, 25, and 30. Serum ovalbumin-specific IgE, IL-13, and melatonin levels were measured on days 1 (baseline), 15, and 30. The nasal mucosa of all rats was scored histopathologically. Results: The total nasal symptom scores and serum ovalbumin-specific IgE values of the SF, ethanol, and melatonin groups were significantly higher on day 15 than those of the control group. On day 30, the scores and serum ovalbumin-specific IgE values of the melatonin group were similar to those of the control, whereas the SF and ethanol groups had statistically higher scores. The histological scores of the SF and ethanol groups were significantly higher than those of the control and melatonin groups, but no significant difference was found between the melatonin and control groups. Conclusion: Melatonin reduced total nasal symptom scores and serum ovalbumin-specific IgE levels and improved histological inflammation parameters in the ovalbumin-induced rat experimental AR model.